Ethnomathematics Study in Elementary School: Integration of Character Values and Mathematics Concepts in Badeng Arts - Sunan, Dani Abdul; Apriliani, Widya; Mutaqin, Ejen Jenal; Suryaningrat, Eko Fajar; Ramdan, Mohammad (Universitas Sebelas Maret, 2025)
This study explores character values and mathematical concepts in the traditional Badeng art of Singajaya District, Garut, and its potential for elementary education through an ethnopedagogical approach. A qualitative ethnographic method was applied using observation, interviews, and documentation. The findings show that Badeng reflects values such as religiosity, responsibility, discipline, cooperation, and cultural appreciation. Mathematical concepts such as patterns, symmetry, rhythm, and measurement are also found in its music and movements. Integrating Badeng into thematic learning can strengthen character education and enhance students’ contextual understanding of mathematics. The study recommends developing culturally rooted thematic learning materials. Penelitian ini bertujuan mengeksplorasi nilai karakter dan konsep matematika dalam kesenian tradisional Badeng di Kecamatan Malangbong, Kabupaten Garut, serta potensinya dalam pembelajaran sekolah dasar berbasis etnopedagogik. Metode yang digunakan adalah kualitatif dengan pendekatan etnografi, melalui observasi, wawancara, dan dokumentasi. Hasil menunjukkan bahwa Badeng mengandung nilai religiusitas, tanggung jawab, disiplin, kerja sama, dan cinta budaya. Konsep matematika seperti pola, simetri, ritme, dan pengukuran juga ditemukan dalam musik dan gerakannya. Integrasi Badeng dalam pembelajaran tematik dapat memperkuat pendidikan karakter dan pemahaman matematika secara kontekstual. Penelitian ini merekomendasikan pengembangan bahan ajar tematik berbasis budaya lokal.